Thermal gradient strategy to improve seeding for high rate zero excess lithium metal batteries - Raj, Abhi; Atkinson, Robert W.; Kingston, Todd A.; Carter, Rachel; Love, Corey T. (Frontiers in Energy Research, 2024)
Zero excess lithium metal batteries (LMBs) have traditionally suffered from short cycle life due to nonuniform processes that result in parasitic side reactions and a subsequent loss of lithium inventory and electrolyte. The experiments herein demonstrate that zero excess LMB cells cycled with a low thermal average and thermal gradient outperform cells cycled under isothermal conditions during early cycles. Specifically, a low thermal average of ∼6.4°C and thermal gradient of <1°C across the cell is shown to increase the overpotential for lithium deposition at the anode current collector, likely resulting in smaller and higher density nucleates, providing film like morphologies observed with microscopy. Improved performance from this approach is demonstrated at high cycling rates (>4C) and mismatched charge/discharge rates. Optimal cycling behavior was observed with 2C charging (30 min) and 3C discharging (20 min). These advantages were translated to the system relevant form factor-pouch cell (20X capacity). Based on the performance enhancement observed with extended application of a thermal gradient, we demonstrate the use of the environment as a formation strategy, to perpetuate improved plating in stripping over the cycle life of zero excess LMBs operating in ambient conditions.